Antipsychotic agent-induced deterioration of the visual system in first-episode untreated patients with schizophrenia maybe self-limited: Findings from a secondary small sample follow-up study based on a pilot follow-up study. (April 2020) - Zhuo, Chuanjun; Ji, Feng; Xiao, Bo; Lin, Xiaodong; Chen, Ce; Jiang, Deguo; Ma, Xiaoyan; Li, Ranli; Liu, Sha; Xu, Yong; Wang, Wenqiang
Highlights: The tudy is the first follow-up study to combine MRI, OCT, and clinical examination for the characterization of changes in visual cortex, retina, and visual perception disturbances in patients with FUSCHVD after three years of treatment with antipsychotic agents. Treatment with antipsychotic agents was associated with structural deterioration in the visual cortex and in the retina and reported exacerbation of subjective experiences of impairments in visual perception disturbances. There was a significant correlation among the extent of deterioration in the visual cortex, the extent of deterioration in the retina, and visual perception disturbance symptoms with the dosage of antipsychotic medication administered. Abstract: Define changes in the visual cortex and retina in first-episode schizophrenia patients with visual disturbance (FUSCHVD) accompanied by antipsychotic agent treatment is important for guiding treatment. We examined the visual system prior to and after 3 years of antipsychotic-agent treatment in 48 patients with FUSCHVD and 50 healthy controls, and after 3.5 years of antipsychotic-agent treatment in 12 patients with FUSCHVD and 12 healthy subjects who came from the cohort with 3 years of follow up. Reduction of the visual cortex gray matter volume (GMV) was observed in patients compared to healthy controls, and impairments deteriorated accompanied with 3 years' treatment with antipsychotic agents. Total retinal thickness was also reduced in patients but did not deteriorated with treatment with antipsychotic agents. However, in the 12 patients who performed the additional 6-month follow-up, GMV and total retinal thickness reductions did not demonstrate any further trend in deterioration. These findings indicate that the reductions of GMV and retinal thickness may be self-limited. Although these findings were consistent with previous reports, it was only observed in a small number of patients. Therefore, clinicians should remain pay greater attention to visual system impairment in FUSCHVD.